Menyiasati Kurikulum dan Pelajaran Sastra Indonesia di Sekolah Kiat untuk Mafhum dan Berbenah - Ibnu Wahyudi (SUSASTRA: Jurnal Ilmu Susastra dan Budaya, 2007)
Cynicism, apathy, inddiference and the like usually accompany the implementation of a new curriculum. The anecdote, "a new minister, a new curriculum” is often heard. Is the ever-changing curriculum meant to create a setback in our education? Of course not.From the perspective of instrumental input, the quality of teachers in Indonesia can safely be said to be low, whereas teachers are the ones who are in charge of implementing the curriculum in the classroom. What about teachers of language and literature? Some articles have revealed that many literature teachers are not keen on reading literature, lag behind in the development of the area, poorly appreciate the dynamics of literature, and many are even foreed to teach literature because they happen to be language teachers.Teachers who only rely on the knowledge or reading they obtained during their school years are definitely not good teachers. The leaming of literature should be far from boredom and fear. Democratization or the process of gaining the freedom of expression essentially begin with the enjoyment and appreciation of literature. There are various tips that can be suggested, such as integrating the teaching of literature and the surrounding environment, class discussion that is not based on the true-false approach, making use of literary texts that have undergone a transfromative process, doing away with the dichotomy of "high" literature and "popular" literature, and students producing their own works to stimulate creativity. By learning and exploring the learning material bascd on necessity and the dynamics of both students and the invironment, there will be a well-patterned method and teaching strategy.